Influence of polyurethane resin dies on the fit and adaptation of full veneer crowns - Graeme R R Lillywhite; Fahim Vohra (Wolters Kluwer Medknow Publications, 2015)
Context: Polyurethane resin is a possible alternative to type IV dental stone for fabrication of indirect restorations however its dimensional accuracy is questionable. Aim: The aim was to investigate the dimensional accuracy of silica filled polyurethane resin die material by evaluating the marginal fit and adaptation of indirect gold castings. Settings and Design: Experimental, in vitro study. Materials and Methods: Totally 40 copper plated replicas of a nickel chrome master die analogous to a veneer gold crown preparation were made and impressions recorded using polyvinylsiloxane material. Twenty impressions were poured in type IV dental stone (control group (Vel-mix, Kerr, UK) and the remaining (n = 20) in silica filled polyurethane die material (test group) (Alpha Die MF, CA, USA). Gold castings were fabricated for each die using standardized techniques. The castings were seated on their respective copper plated dies, embedded in resin and sectioned. The specimens were analyzed by measuring marginal opening and the area beneath the casting at a ×63 magnification and using image analysis software. Statistical Analysis Used: Data were analyzed using a Student's t-test. Results: No significant difference was observed between the experimental groups (P > 0.05). The mean marginal opening for type IV, dental stone and polyurethane resin, was 57 ± 22.6 μm and 63.47 ± 27.1 μm, respectively. Stone displayed a smaller area beneath the casting (31581 ± 16297 μm 2 ) as compared to polyurethane resin (35003 ± 23039 μm 2 ). Conclusions: The fit and adaptation of indirect gold castings made on polyurethane and type IV dental stone dies were comparable.